2022
DOI: 10.3390/foods11121818
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols and Polysaccharides from Morus alba L. Fruit Attenuate High-Fat Diet-Induced Metabolic Syndrome Modifying the Gut Microbiota and Metabolite Profile

Abstract: Morus alba L. fruit, a medicinal and edible fruit in East Asia, showed potential health-promoting effects against metabolic syndrome (MetS). However, both the protective effects and mechanism of different fractions extracted from Morus alba L. fruit against MetS remain unclear. Additionally, the gut microbiota and its metabolites are regarded as key factors in the development of MetS. This study aimed to investigate the potential role of polyphenols and polysaccharides derived from Morus alba L. fruit against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Moreover, F. prausnitzii can produce large amounts of SCFAs, especially butyrate, which is secreted into the intestinal lumen [ 103 ]. Bacteria from the Lachnospiraceae family were observed to maintain the integrity of the intestinal barrier in mice, and their abundance was negatively correlated with chronic kidney disease [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, F. prausnitzii can produce large amounts of SCFAs, especially butyrate, which is secreted into the intestinal lumen [ 103 ]. Bacteria from the Lachnospiraceae family were observed to maintain the integrity of the intestinal barrier in mice, and their abundance was negatively correlated with chronic kidney disease [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…Alistipes is a member of the Bacteroidetes phylum, Rickenellaceae family, known to be an SCFA producer; its low abundance is associated to patients with non-alcoholic fat liver disease and liver fibrosis. However, it may be pathogenic in anxiety disorders, chronic fatigue syndrome, and depression, although it exerts a protective role in the health phenotype [ 104 ]. The Flintibacter genus is characterized by rod-shaped, Gram-negative bacteria from the Ruminococcaceae family.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, our results demonstrated that HD-QRQZ could regulate the disordered gut microbiota in NASH mice, and this alteration may have a potential association with improved lipid metabolism. Besides, aqueous extract of Morus alba L. could reinforce Muribaculaceae while polyphenols and polysaccharides from Morus alba L. could increase Lachnospiraceae_NK4A136_group and decrease Faecalibaculum in mice fed with HFD ( 66 , 67 ). Coptis chinensis Franchcan could increase the abundance of Blautia in ulcerative colitis rats ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous R&D achievements have been reported on obesity and its treatment to date, problems associated with obesity have not yet been fully addressed. Several studies have reported the inhibitory effects of silkworms and silkwormrelated sericultural products, such as silkworms on the 3rd day of the 5th instar larvae [17], silk peptide (SP) [18], silk sericin [19,20], silkworm pupa peptide [18,21], and mulberry leaves [22,23] and fruits [24], on obesity and/or BW gain (BWG). However, obesity-related activities have not yet been reported for MS or SMSP.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous obesity-related in vivo animal studies, the age of the mice at the start of long-term drug treatment varied from study to study. In many studies, in fact, long-term administration of test agents was initiated in mice younger than 10 weeks of age [19][20][21][22][23][24][25][26][27][28]. Adulthood in animals is biologically defined as the age at which sexual maturity is attained.…”
Section: Introductionmentioning
confidence: 99%